Time‐resolved particle image velocimetry analysis and computational modeling of transient optically induced electrothermal micro vortex. Issue 23 (29th August 2021) - Gupta, Kshitiz; Chen, Zhengwei; Williams, Stuart J.; Wereley, Steven T.
Abstract: Trapping, sorting, transportation, and manipulation of synthetic microparticles and biological cells enable investigations in their behavior and properties. Microfluidic techniques like rapid electrokinetic patterning (REP) provide a non‐invasive means to probe into the nature of these micro and nanoparticles. The opto‐electrically induced nature of a REP micro vortex allows tuning of the trap characteristics in real‐time. In this work, we studied the effects of transient optical heating on the induced electrothermal vortex using micro‐particle image velocimetry (μ‐PIV) and computational modeling. A near infra‐red (980 nm) laser beam was focused on a colloidal suspension of 1 μm polystyrene beads sandwiched between two parallel‐plate electrodes. The electrodes were subjected to an AC current. The laser spot was scanned back‐and‐forth in a line, at different frequencies, to create the transient vortex. This phenomenon was also studied with a computational model made using COMSOL Multiphysics. We visualize fluid flow in custom‐shaped REP traps by superposing multiple axisymmetric (spot) vortices and discuss the limitations of using superposition in dynamically changing traps.